Frontiers in Optics 2010/Laser Science XXVI 2010
DOI: 10.1364/fio.2010.fthn1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Spatial Coherence on the Angular Distribution of Radiant Intensity Generated by Scattering on a Sphere

Abstract: In the analysis of light scattering on a sphere it is implicitly assumed that the incident field is spatially fully coherent. However, under usual circumstances the field is partially coherent. We generalize the partial waves expansion method to this situation and examine the influence of the degree of coherence of the incident field on the radiant intensity of the scattered field in the far zone. We show that when the coherence length of the incident field is comparable to, or is smaller than, the radius of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The coherence characteristics of a light source affect the properties of the propagated field and, in particular, its irradiance profile, so that it is also possible to tune the beam shape by controlling the coherence of the source [1][2][3][4][5][6][7][8][9]. Such a feature is of a great interest in those applications, such as in remote sensing [10], free space optical communications [11][12][13], or optical trapping [14,15], just to mention some examples where the use of partially coherent sources have been proposed, due to the advantages they present if compared to their coherent counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…The coherence characteristics of a light source affect the properties of the propagated field and, in particular, its irradiance profile, so that it is also possible to tune the beam shape by controlling the coherence of the source [1][2][3][4][5][6][7][8][9]. Such a feature is of a great interest in those applications, such as in remote sensing [10], free space optical communications [11][12][13], or optical trapping [14,15], just to mention some examples where the use of partially coherent sources have been proposed, due to the advantages they present if compared to their coherent counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…7implies that, as long as β2a < 2.4, the function J 0 will be positive and the cross-spectral density function between all possible pairs of points within the scatterer will be qualitatively similar to a Gaussian. It is known from earlier studies [16] that, for such a correlation function, the scattering remains predominantly in the forward direction, i.e., θ max 0°. Only when β2a > 2.4 will there be pairs of points that are negatively correlated, which gives rise to a qualitatively different scattering profile.…”
Section: Suppression Of Forward Scatteringmentioning
confidence: 97%
“…They derived conditions under which the forward or backward scattering by magnetic spheres is strongly suppressed. Since then, both the influence of the particle's composition [5][6][7][8][9][10][11] and that of the coherence properties of the incident field on the scattering process have been examined [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Note that equivalent expressions for the autocorrelation dyadics, to those obtained by using (17), would be derived by utilizing the popular Gaussian Schell-model form for W i ab [19,20] and then evaluating two of the plane-wave spectrum integrals asymptotically assuming that the incident-field spectral density widths become very large. This approach was utilized by Fischer et al in analyzing the effects of field coherence on the far-zone scattering from spheres [32,33].…”
Section: Approximations and Simplificationsmentioning
confidence: 99%
“…Beginning with Wolf's unified theory of coherence and polarization [19], techniques have been developed and demonstrated that produce light with practically any desired shape, coherence, and polarization properties [20][21][22]. Much research has been performed predicting how these partiallycoherent fields propagate through random media [20,[23][24][25][26][27], scatter from deterministic and random objects [19,20,[28][29][30][31][32][33][34][35], and propagate through anisotropic media [36][37][38][39]. To the U.S. Government work not protected by U.S. copyright Figure 1.…”
Section: Introductionmentioning
confidence: 99%